Dental Mesenchymal Stem Cell-Based Translational Regenerative Dentistry: From Artificial to Biological Replacement - Marei, Mona K.; El Backly, Rania M. (Frontiers in Bioengineering and Biotechnology, 2018)
Dentistry is a continuously changing field that has witnessed much advancement in the past century. Prosthodontics is that branch of dentistry that deals with replacing missing teeth using either fixed or removable appliances in an attempt to simulate natural tooth function. Although such “replacement therapies” appear to be easy and economic they fall short of ever coming close to their natural counterparts. Complications that arise often lead to failures and frequent repairs of such devices which seldom allow the true physiological function of dental and oral-maxillofacial tissues. Such factors can critically affect the quality of life of an individual. The market for dental implants is continuously growing with huge economic revenues. Unfortunately, such treatments are again associated with frequent problems such as peri-implantitis resulting in an eventual loss or replacement of implants. This is particularly influential for patients having co-morbid diseases such as diabetes or osteoporosis and in association with smoking and other conditions that undoubtedly affect the final treatment outcome. The advent of tissue engineering and regenerative medicine therapies along with the enormous strides taken in their associated interdisciplinary fields such as stem cell therapy, biomaterial development, and others may open arenas to enhancing tissue regeneration via designing and construction of patient-specific biological and/or biomimetic substitutes. This review will overview current strategies in regenerative dentistry while overviewing key roles of dental stem cells particularly those of the dental pulp, until paving the way to precision/translational regenerative medicine therapies for future clinical use.